The Role of Microbiomes in Pregnant Women and Offspring: Research Progress of Recent Years - Yao, Yao; Cai, Xiaoyu; Chen, Chunyan; Fang, Hui; Zhao, Yunchun; Fei, Weidong; Chen, Fengying; Zheng, Caihong (Frontiers in Pharmacology, 2020)
Pregnancy is a complicated and delicate process, the maternal body undergoes changes on hormones, immunity and metabolism during pregnancy to support fetal development. Microbiomes in the human body mainly live in the intestine, and the human gut microbiomes are complex, which composed of more than 500 to 1500 different bacteria, archaea, fungi and viruses. Studies have shown that these microbiomes are not only involved in the digestion and absorption of food, but also indispensable in regulating host health. In recent years, there has been increasing evidence that the microbiomes are important for pregnant women and fetuses. During pregnancy, there will be great changes in gut microbiomes. Regulating gut microbiomes is beneficial to the health of the mother and the fetus. In addition, many complications during pregnancy are related to gut microbiomes, such as gestational diabetes, obesity, preeclampsia, digestive disorders, autoimmune diseases. Moreover, the microbiomes in mother's milk and vagina are closely related to the colonization of microbiomes in the early life of infants. In this review, we systematically review the role of maternal microbiomes in different gestational complications, and elucidate the function and mechanism of maternal microbiomes in the neural development and immune system of offspring. These will provide a clear knowledge framework or potential research direction for researchers in related fields.